AGV Task Distribution Study. Issue 7 (April 2020) - Wu, Guorong; Sun, Xuan
Abstract: In this paper, the traditional AGV task allocation mechanism assigns tasks with large path cost and low operational efficiency. A single AGV dual task allocation mechanism based on task priority and FCFS is designed. By changing the order and distribution mode of the main categories of tasks, the mechanism assigns two different kinds of tasks to the AGV, which reduces the empty vehicle operation caused by the continuous execution of similar tasks by the AGV, thereby reducing the path cost and improving the operational efficiency of the AGV system. The open-TCS simulation calculation uses this method to increase the operating efficiency of the AGV system by 20%.